2022
DOI: 10.3389/fphar.2022.942032
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of the Rehmannia glutinosa Libosch and Cornus officinalis Sieb herb couple on chronic kidney disease rats via modulating the intestinal microbiota and enhancing the intestinal barrier

Abstract: CKD is a clinical syndrome with slow development and gradual deterioration of renal function. At present, modern medicine still lacks an ideal treatment method for this disease, while TCM has accumulated rich clinical experience in the treatment of CKD, which can effectively improve renal function and delay renal failure, and has unique advantages. RC is widely used in clinical practice to treat CKD, especially the “Kidney-Yin” deficiency syndrome. However, the compatibility mechanisms responsible for its effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Future studies examining the impact of CO on T1D should incorporate additional immunological markers such as examination of T‐cell subsets, generation of Regulatory T cells (Tregs), and the impact on lymphocyte trafficking. Other studies have demonstrated that administration of CO in animal models can alter the intestinal microbiome and promote various metabolic effects [ 37 , 38 ]. Therefore further examination should be performed elucidating any changes in the gut microbiome during CO administration.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies examining the impact of CO on T1D should incorporate additional immunological markers such as examination of T‐cell subsets, generation of Regulatory T cells (Tregs), and the impact on lymphocyte trafficking. Other studies have demonstrated that administration of CO in animal models can alter the intestinal microbiome and promote various metabolic effects [ 37 , 38 ]. Therefore further examination should be performed elucidating any changes in the gut microbiome during CO administration.…”
Section: Discussionmentioning
confidence: 99%
“…HQ, DH, and SQ have been shown to exhibit reno-protective effects in kidney diseases. [20][21][22] Meanwhile, the main active component of BS (total glucosides of paeony) and NBZ (arctigenin) have been shown to have therapeutic effects in CKD. 23,24 However, the mechanism by which QBF improves renal dysfunction in DKD remains unclear.…”
Section: Introductionmentioning
confidence: 99%